Menentukan Sistem Persamaan Linear dalam Bentuk Konsisten dan Inkonsisten - Daliyah Narayani (PT PUSTAKA CENDEKIA GROUP, 2024)
A linear equation is an equation where the variables involved have a degree of at most one.A linear equation isa linear equation with n variables x1, x2, ... , xn. If we have several linear equations then the set of linearequations is called a system of linear equations. This article will explain how to determine a system of linearequations in consistent and inconsistent form. The information gathering method used is literature study. Bydetermining a system of linear equations into consistent and inconsistent forms, students can distinguish asystem of equations.